Role of breast ultrasound, mammography, magnetic resonance imaging and diffusion weighted imaging in predicting pathologic response of breast cancer after neoadjuvant chemotherapy - Manal Hamisa; Naglaa Dabess; Raghda Yosef; Fatma Zakeria; Qanet Hammed (The Egyptian Journal of Radiology and Nuclear Medicine, 2015)
Background: Breast cancer is the most common cancer affecting females worldwide, patient who present with late stage disease, will be treated initially with neoadjuvant chemotherapy to downstage the disease. Aim: To evaluate the ability of mammography, US and MRI in assessment of residual tumor and the real extent of the disease after neoadjuvant chemotherapy. Methods: Thirty patients proved with locally advanced breast cancer and received neoadjuvant chemotherapy. All patients underwent mammograms, US, MRI of both breast before and after 3 cycles chemotherapy. Results at end of treatment mammography detect 20 operable lesions ranging size (3–9.5 cm) with mean 5.7 cm. Ultrasound detect 30 lesions ranging size (2–6.8 cm) with mean size 2.75 cm. MRI detected 30 lesions ranging size (1.8–7.4 cm) with mean 3.5 cm. Mammography overestimated the actual size of residual tumor in 16 cases (80%) and underestimated the size in 4 cases (20%). US overestimated the actual size in 6 (20%), underestimated size in 22 lesions (73.3%). MRI overestimated the actual size in 20 lesions (66.7%), underestimated in 7 lesion (23.3%). Conclusion: MRI is accurate than mammography and ultrasound in detection the actual pathologic size of cancer breast and also in predicting the residual disease after neoadjuvant chemotherapy.